2017
DOI: 10.1177/0971890717736211
|View full text |Cite
|
Sign up to set email alerts
|

Financial Market Development and Bank Capitalization Ratio

Abstract: Financial sector liberalization in many African countries, set in a series of financial sector reforms, aimed at developing the system. Theoretically, reforms that develop the banking sector are expected to improve banks’ performance and reduce excessive bank-risk taking by enhancing bank capital ratio in addition to maintain the stability in the system. Nonetheless, literature also shows that the health of the financial system may be at risk following a liberalization process in the form of contagion effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The non-significance of AR (2) shows the absence of serial correlation in differenced residuals, while that of Hansen indicates that the instruments used are valid and the model is not over-identified. Furthermore, the positive and significant coefficients for the lagged bank capital justify the use of a dynamic model and the presence of adjustment costs that may hinder a bank from instantaneous change in capital ratio, consistent with earlier arguments of Brei and Gambacorta (2016), Ozili (2015) and Etudaiye-Muhtar et al (2017).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The non-significance of AR (2) shows the absence of serial correlation in differenced residuals, while that of Hansen indicates that the instruments used are valid and the model is not over-identified. Furthermore, the positive and significant coefficients for the lagged bank capital justify the use of a dynamic model and the presence of adjustment costs that may hinder a bank from instantaneous change in capital ratio, consistent with earlier arguments of Brei and Gambacorta (2016), Ozili (2015) and Etudaiye-Muhtar et al (2017).…”
Section: Resultssupporting
confidence: 82%
“…It is equally important to note that Eqn (1) is a partial adjustment model that accounts for adjustment costs which arises when banks try to adjust to meet capital requirements. High adjustment costs may prevent banks from instantaneous change in capital when they fall short of regulatory requirements, making them liable to penalties (Brei and Gambacorta, 2016; Etudaiye-Muhtar et al , 2017; Ozili, 2015). To avoid this situation, banks would need to increase the capital ratio, and a positive and significant coefficient of the lagged capital ratio would indicate the presence of adjustment costs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, according to our knowledge, literatures that investigates the effect of development in the banking sector on bank risk-taking behaviour specifically for developing countries is scarce and have ambiguous result. For instance, Abdulhamid et al (2019); Etudaiye-Muhtar et al (2017) found that banking sector development reduce banks' risk-taking while Vithessonthi (2014a) observes that there is positive effect of banking sector development on banks' risk-taking behaviour in Southeast Asia region. Because of the ambiguity of results and scarcity of research on banking sector development and bank-risk taking behaviour in developing countries, this contribute to the main motivation for this study which examine the effect of banking sector development on bank risk-taking behaviour measured in terms of capitalization ratio in Tanzania to find more evidence for developing countries.…”
Section: Background Of the Studymentioning
confidence: 99%